Haematological parameters, natural regulatory CD4 + CD25 + FOXP3+ T cells and γδ T cells among two sympatric ethnic groups having different susceptibility to malaria in Burkina Faso - Sanou Guillaume S (BMC Research Notes, 2012)
Abstract Background Fulani ethnic group individuals are less susceptible than sympatric Mossi ethnic group, in term of malaria infection severity, and differ in antibody production against malaria antigens. The differences in susceptibility to malaria between Fulani and Mossi ethnic groups are thought to be regulated by different genetic backgrounds and offer the opportunity to compare haematological parameters, Tregs and γδT cell profiles in seasonal and stable malaria transmission settings in Burkina Faso. The study was conducted at two different time points i.e. during the high and low malaria transmission period. Results Two cross-sectional surveys were undertaken in adults above 20 years belonging either to the Fulani or the Mossi ethnic groups 1) at the peak of the malaria transmission season and 2) during the middle of the low malaria transmission season. Full blood counts, proportions of Tregs and γδ T cells were measured at both time-points. As previously shown the Fulani and Mossi ethnic groups showed a consistent difference in P. falciparum infection rates and parasite load. Differential white blood cell counts showed that the absolute lymphocyte counts were higher in the Mossi than in the Fulani ethnic group at both time points. While the proportion of CD4+CD25high was higher in the Fulani ethnic group at the peak of malaria transmission season (p = 0.03), no clear pattern emerged for T regulatory cells expressing FoxP3+ and CD127low. However CD3+γδ+ subpopulations were found to be higher in the Fulani compared to the Mossi ethnic group, and this difference was statistically significant at both time-points (p = 0.004 at low transmission season and p = 0.04 at peak of transmission). Conclusion Our findings on regulatory T cell phenotypes suggest an interesting role for immune regulatory mechanisms in response to malaria. The study also suggests that TCRγδ + cells might contribute to the protection against malaria in the Fulani ethnic group involving their reported parasite inhibitory activities.